#Bookfairs: New 'old' media and the digital politics of Somali literary promotion. (November 2019) - Chonka, Peter
Since 2008, Book Fairs held across the Somali Horn of Africa have been a remarkable feature of civil society activism in a region usually associated with conflict and crisis. At the forefront of these efforts to promote Somali-language print culture is a digitally connected and social media-savvy generation of young people. This article explores the work done by books (as symbolic objects) and Book Fairs (as multimedia cultural festivals) to provide spaces for debate about Somali identities. Attention to local histories of media development is necessary for understanding the relationships that exist between print and digital culture, and the destabilisation of clear temporal distinctions between 'old' and 'new' media technologies. This participant-observation based study shows how the contemporary social media environment affects the ways in which print culture is promoted – facilitating cross-border civil society networks, and intensifying the political salience of literary activism for actors articulating different visions of Somali statehood.